2017
DOI: 10.14710/jnc.v6i4.18249
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Konsumsi Asam Lemak Omega-3, Aktivitas Fisik Dan Persen Lemak Tubuh Dengan Tingkat Dismenore Pada Remaja

Abstract: Background: Dysmenorrhea or menstrual pain was a gynecological complaint due to an imbalance of progesterone in the blood resulting in pain. A woman with dysmenorrhea should consume food rich in omega-3 fatty acids such as fish oil, fish (salmon, tuna, mackerel, herring), soybeans and fruits. Low fish consumption was related with severity of dysmenorrhea. In addition, physical activity and percent body fat were also associated with severity of dysmenorrhea.Objective : To determine the correlation between consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
4
2
2
Order By: Relevance
“…21 Excess adipose tissue associated with fat in the body will increase the ratio of estrogen and progesterone, some researchers prove that level of estrogen circulating in the luteal phase can increase the production of excessive prostaglandins specifically PGF2α and PGE2. 30 However, this study found no association between overweight and obesity and the development of primary dysmenorrhea. Ideal BMI will reduce the severity of dysmenorrhea.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…21 Excess adipose tissue associated with fat in the body will increase the ratio of estrogen and progesterone, some researchers prove that level of estrogen circulating in the luteal phase can increase the production of excessive prostaglandins specifically PGF2α and PGE2. 30 However, this study found no association between overweight and obesity and the development of primary dysmenorrhea. Ideal BMI will reduce the severity of dysmenorrhea.…”
Section: Discussioncontrasting
confidence: 67%
“…This can lead to the hyperplasia of blood vessels or pressure of blood vessels by fat tissue in the female reproductive organs, interrupting the flow of blood during the menstrual process and causing pain during menstruation 21 . Excess adipose tissue associated with fat in the body will increase the ratio of estrogen and progesterone, some researchers prove that level of estrogen circulating in the luteal phase can increase the production of excessive prostaglandins specifically PGF2α and PGE2 30 . However, this study found no association between overweight and obesity and the development of primary dysmenorrhea.…”
Section: Discussioncontrasting
confidence: 58%
“…Fat content in F2 is lower than SNI and commercial snackbars. One of the roles of fat for young women is to reduce dysmenorrhea during menstruation and make the menstrual cycle more regular (20).…”
Section: Analysis Of Nutrition Contentmentioning
confidence: 99%
“…Data aktivitas fisik pada kelompok ini menunjukkan responden paling banyak mengalami aktivitas fisik sedang yaitu 26 orang (51%), aktivitas fisik ringan 14 orang (27,5%), sedangkan yang mengalami aktivitas fisik berat 11 orang (21,6%). Dilihat dari data nyeri dysmenorrhea mayoritas responden pada kelompok ini mengalami nyeri dysmenorrhea kategori sedang yaitu 21 orang (41,2%), kategori ringan 15 orang (29,4), sedangkan yang mengalami nyeri dysmenorrhea kategori berat yaitu 15 orang (29,4%). Sedang 51 100 Berdasarkan Tabel 3. karakteristik responden untuk uji hubungan antara persentase lemak dan nyeri dysmenorrhea bahwa ada 51 responden yang masuk kedalam kelompok ini dan memiliki aktivitas fisik sedang.…”
Section: Hasilunclassified
“…Kadar esterogen dan progesteron meningkat menyebabkan produksi prostaglandin tinggi sehingga terjadi peningkatan aktivitas myometrium dan iskemia yang akan memicu timbulnya nyeri dysmenorrhea. 4 Peneliti lain juga sejalan dengan hal tersebut seperti penelitian yang dilakukan oleh Zivanna et al 11 dan Karina et al 12 menyatakan bahwa kelebihan jaringan lemak didalam tubuh memicu terjadinya dysmenorrhea. Hasil penelitian tersebut berbeda dengan penelitian yang dilakukan oleh Gustini et al 13 yang menyatakan bahwa tidak terdapat hubungan bermakna antara masa lemak dengan kejadian dysmenorrhea.…”
unclassified